1998
DOI: 10.1074/jbc.273.1.80
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Interaction between the Cardiac Sodium Channel and Site-3 Toxin Anthopleurin B

Abstract: The polypeptide neurotoxin anthopleurin B (ApB) isolated from the venom of the sea anemone Anthopleura xanthogrammica is one of a family of toxins that bind to the extracellular face of voltage-dependent sodium channels and retard channel inactivation. Because most regions of the sodium channel known to contribute to inactivation are located intracellularly or within the membrane bilayer, identification of the toxin/channel binding site is of obvious interest. Recently, mutation of a glutamic acid residue on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 40 publications
1
99
0
3
Order By: Relevance
“…ApB substantially enhances VGSC currents by selectively impairing fast inactivation (Benzinger et al, 1998). We found that ApB significantly enhanced the gating-pore currents generated in DIV (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…ApB substantially enhances VGSC currents by selectively impairing fast inactivation (Benzinger et al, 1998). We found that ApB significantly enhanced the gating-pore currents generated in DIV (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…The pores of such channels have been mapped by analysis of their interactions with conotoxins (Na V ) and a variety of polypeptides from scorpion venoms, such as charybdotoxin and agitoxins (1)(2)(3)(4). More recently, regions of these channels involved in gating have been identified by using gating modifier toxins derived from scorpion (5), sea anemone (6), and spider (7)(8)(9) venoms. Most interestingly, gating modifier toxins appear to interact with the same channel region, designated the S3-S4 linker, irrespective of the type of channel being studied (10).…”
mentioning
confidence: 99%
“…ApB is a 49-amino acid residue polypeptide toxin that functions to delay channel inactivation upon binding to site 3 of Na V s (13), where it competes with a number of scorpion ␣-toxins that have functionally identical effects. Site 3 has been mapped by mutant cycle analysis to the S3-S4 linker of Na V domain IV (5,6). ProTx-II (PT-II) is a recently discovered 30-amino acid residue polypeptide that conforms to the inhibitory cysteine knot motif and functions as a gating modulator to inhibit Na V activation (14).…”
mentioning
confidence: 99%
“…These gating modifier toxins bind to sites 3 and 4, respectively. Site 3 has been localized to the extracellular S3/S4 linker of domain IV (9,10), whereas residues in domain II S3/S4 make a major contribution to site 4 (11,12).…”
mentioning
confidence: 99%